2022
DOI: 10.3889/oamjms.2021.7835
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Spiritual Caring with Quality of Live for Hemodialysis Patients: A Literature Review

Abstract: BACKGROUND: The frequency of hemodialysis therapy routinely affected change in the functional state of the body. Support is one of the factors that can affect life quality. One of the supports can come from nurses through a spiritual caring attitude. AIM: The purpose of this study is to determine the relationship between spiritual caring and the life quality of patients who were undergoing hemodialysis. METHOD: A literature review was obtained from PubMed and Google Scholar databases (2015–2020) with the k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Previous studies have indicated that patients with advanced kidney disease often have numerous unmet spiritual needs. Furthermore, higher levels of spirituality have been linked to greater QoL across physical, psychological, social, and environmental domains [ 28 ]. Scherer et al [ 29 ] conducted a survey of 927 American patients undergoing dialysis and discovered that those who placed greater importance on religious or spiritual beliefs were more inclined to favor resuscitation, tended to prefer a shared decision-making role, and were less likely to have considered or discussed the cessation of dialysis.…”
Section: Symptom Burden and Palliative Care Needs Of Patients Undergo...mentioning
confidence: 99%
“…Previous studies have indicated that patients with advanced kidney disease often have numerous unmet spiritual needs. Furthermore, higher levels of spirituality have been linked to greater QoL across physical, psychological, social, and environmental domains [ 28 ]. Scherer et al [ 29 ] conducted a survey of 927 American patients undergoing dialysis and discovered that those who placed greater importance on religious or spiritual beliefs were more inclined to favor resuscitation, tended to prefer a shared decision-making role, and were less likely to have considered or discussed the cessation of dialysis.…”
Section: Symptom Burden and Palliative Care Needs Of Patients Undergo...mentioning
confidence: 99%
“…The patient's perception of caring from the aspect of spirituality is related to general quality of life and aspects of general health, physical, psychological and environmental (13). Spiritual interventions affect the quality of life of hemodialysis patients (14).…”
Section: Introductionmentioning
confidence: 99%